Insight into Yeast–Mycotoxin Relations - László Attila Papp; Enikő Horváth; Ferenc Peles; István Pócsi; Ida Miklós (Agriculture, 2021)
Fungal mycotoxins are secondary metabolites that can be present in green forage, hay, or silage. Consumption of contaminated plants or agricultural products can cause various animal and human diseases, which is why problems associated with mycotoxins have received particular attention. In addition, public pressure to produce healthy food and feed is also increasing. As the results of several surveys indicate that yeasts can decrease toxic effects by binding or converting secondary metabolites or control growth of harmful fungi, this article provides an overview of the yeast species that can have great potential in detoxification. The most important antagonistic yeast species against toxigenic fungi are described and the mode of their inhibitory mechanisms is also discussed. We provide an insight into toxin binding and biotransformation capacities of yeasts and examples of their use in silo. Issues requiring further study are also mentioned.